USE OF PHYTOTHERAPY IN PORTUGAL: RESULTS FROM AN ONLINE SURVEY - Aguiar, Rui; Martins, Alexandra; Scholz, Sonia; Amaral, Teresa; Frazao, Joana (Health and Society, 2023)
The objective of this work is to better understand the use of plants and herbal products for medicinal purposes in Portuguese households, namely which plants are most used and which health conditions are most targeted. It also seeks to evaluate the attitudes and habits related to this use, its role in their health management, the sources of information used and the frequency of consultation with professionals specialized in the area. A descriptive cross-sectional study was conducted using an online questionnaire. A total of 210 responses were obtained. 78% of the respondents were female. 71.9% of the respondents had a university degree. 41.4% reported having salary above € 1000 and 27.1% above € 2000. The mean age in the sample was 50.8 years. More than 50% of the respondents reported using medicinal plants in the flu and cough, to aid digestion and to aid sleep. The plants with more respondents were eucalyptus and peppermint (in respiratory conditions), lemon balm (in digestive and nervous conditions), chamomile (in respiratory, digestive and skin conditions), linden (in respiratory and nervous conditions), rosemary (for digestive, circulatory and nervous diseases) and arnica (for joint and skin diseases). The most common form of use was infusion (87.6%), followed by essential oils (51.0%), tablets or similar forms (48.1%) and external forms (46.7%). The most frequent places of acquisition of medicinal plants were the stores of natural products (71.4%). 31.4% of the respondents put medicinal plants as the first option in their health management, and 30.5% said they used them together with conventional medicines. The main sources of information for decisions on this topic mentioned by the sample were family knowledge (54.8%), consultations with naturopaths and similar (41.9%), counseling with friends (37.1%), specialized means in natural health (35.2%) and generalist means (34.3%). 23.8% of the respondents said they make consultations with phytotherapy professionals or naturopaths, while 23.3% said they do it only in severe cases. This study found a substantial use of medicinal plants in Portugal, especially for the mildest health conditions and with the safest plants. The evaluation of the answers in the face of scientific knowledge about the properties of plants points to a mostly correct use. However, the issues of adverse reactions, contraindications and drug interactions were not addressed in this study. We recognize that a reasonably detailed web questionnaire is answered mainly by the people with the most interest in the subject, and therefore the sample obtained may not be representative of the general Portuguese population. Bearing in mind that fact, this study will still provide useful information the most used plants and target conditions, as well as on the usage patterns of the people who use them the most.